The Influence of Intrinsic and Extrinsic Motivation on Performance Through Satisfaction at Brawijaya Hospital Saharjo - Nesha Yama Ramadhani; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study was to determine and analyze the effect of intrinsic and extrinsic motivation on performance through satisfaction at Brawijaya Saharjo Hospital. This study uses a quantitative approach using primary data types. The sampling technique was carried out using the census method and all members of the population were used as research samples. Sampling was carried out using a questionnaire distributed via Google Forms. Data on nurses who were successfully interviewed amounted to 275 samples. The data analysis model used in this study is Structural Equation Modeling (SEM) using SmartPLS 3.0. The results of the study tested the hypotheses and found that (1) intrinsic motivation has a positive and significant effect on job satisfaction, (2) extrinsic motivation has a positive and significant effect on job satisfaction, (3) intrinsic motivation has a positive and significant effect on nurse performance, (4) extrinsic motivation has no effect on nurse performance, (5) job satisfaction has a positive and significant effect on nurse performance, (6) intrinsic motivation has a positive and significant effect on nurse performance through job satisfaction, (7) extrinsic motivation has a positive and significant effect on nurse performance through job satisfaction.These results highlight the importance of intrinsic and extrinsic motivation in efforts to improve job satisfaction and performance of nursing staff.